Developing E-Commerce Regulatory Standards for Online Dispute Resolution - Muthia Sakti (Journal of Morality and Legal Culture, 2021)
Disputes involving losses or defaults suffered Prolong the process and create uncertainty for the company or the disputing parties. Consequently, alternative dispute resolution facilitates the dispute resolution process for online transactions. One is to provide alternative dispute resolution via Online Dispute Resolution (ODR). The Method study employs the descriptive-analytic approach to acquire in-depth data that will be meaningful. This study intends to examine the opportunities and challenges faced by buyers in using Online Dispute Resolution. Concluded Although juridically, the Arbitration and Alternative Dispute Resolution Law do not regulate ODR, Some forms of legal discovery that can be done are interpretation and analogy to explain the provisions of the articles in the Arbitration Law and Alternative Dispute Resolution.